Analisis Konsep Knowledge Management dalam Kajian Manajemen Pendidikan Islam - Safinah; Muhammad Ali Jum’ah Rahmatullah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The development of a knowledge-based society demands that Islamic educational institutions manage knowledge systematically and sustainably. However, the practice of managing Islamic education still tends to focus on administrative and structural aspects, while the management of knowledge as a strategic asset has not been optimal. This study aims to analyze the concept of Knowledge Management within the study of Islamic Education Management and to examine its relevance as a strategy for improving the quality of Islamic educational institutions based on values. This research uses a qualitative approach with library research as the type of study. Data were obtained from books, scholarly journal articles, and relevant publications, which were analyzed using content analysis in a descriptive-analytical manner. Research results indicate that Knowledge Management is closely related to Islamic Education Management, particularly in the management of human resources, organizational culture, and utilization of information technology. The implementation of Knowledge Management integrated with Islamic values such as amanah (trustworthiness), ihsan (excellence), itqan (proficiency), and mas’uliyyah (responsibility) can strengthen the learning organization culture, enhance learning innovation, and support knowledge-based decision-making